Beliefs, values, and traditions: re-thinking sustainable development using the Hñähñu example. Issue 1 (2nd January 2019) - Lugo-Morin, Diosey Ramon; Garcia-Sanchez, Enoc; Cruz-Vazquez, Rosa Isela
ABSTRACT: Historically humans have used their territorial resources to meet their reproductive needs. In doing so, they have developed informal institutions through their systems of beliefs and values that have determined the sustainability of the resources they use from their environment. In this sense, this article evaluates the artisanship of the Hñähñu indigenous group as a case study that potentially help us to re-conceptualise sustainable development.